A Quality-Based Educational Marketing Strategy to Increase Student Interest - Muaz Muaz; Nina Nurmila; Bambang Qomaruzzaman; Hasan Basri (International Journal of Islamic Educational Research, 2025)
The competition among educational institutions demands improvement in service quality as a key marketing strategy. Good service quality not only builds a positive image for the institution, but also encourages student satisfaction and interest. The purpose of this study is to identify a quality-based educational marketing strategy to increase student interest. This study used a qualitative approach, with a case study method. Data collection techniques were conducted through interviews, observation, and documentation analysis. The results of the study found that: 1) An effective Islamic education marketing strategy is rooted in the integration of Islamic values and service quality as the basis for forming a positive image of the institution. 2) MTs Al Hidayah excels with a humanistic approach based on empathy and service flexibility, while MTs Daarul Uluum PUI excels through a structured and institutional quality management system. 3) Visionary leadership, teacher competence, and spiritual value-based communication are key factors in building public trust and loyalty. 4) The main obstacles include a lack of quality systematization, documentation, and digital promotion innovation, which have an impact on the limited reach and professionalism of marketing. Strategic solutions include strengthening data-based quality management, increasing human resource capacity, community partnerships, and optimizing digital communication to create sustainable Islamic education marketing that has da'wah value.